Hydrogen as fuel: a critical technology? - Baykara, SZ (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
The potential of hydrogen energy technologies for being recognized as critical technologies (CTs) in the context of sustainable development is briefly discussed in view of the assessment approach and definitions accepted pertaining to CTs by the institutions dedicated to science and technology policy development. The concepts of sustainable development, the relationship between the level of national income and the extent of energy utilisation, CTs in general and national CTs (NCTs) are considered for different types of countries at different stages of economic development. Views of industry and business sectors on CTs and the roles of governments and universities are emphasized. The influence of public acceptance of hydrogen as a fuel is included. It is concluded that in addition to its exceptionally constructive environmental impact at the local, regional and global levels: hydrogen is expected to bring about a substantial change in the present state of affairs by creating a large number of new and diverse technologies, vast employment opportunities in all sectors and by delivering highly efficient and decentralized energy utilisation, free of geopolitical dependence in most cases. In this regard, though hydrogen is considered as a possibility presently, in the near future hydrogen energy technologies will inevitably be recognised as CTs for countries that are consciously adjusting for sustainable development. (c) 2004 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
Keywords: hydrogen energy technologies; critical technologies; critical technology foresighting; science and technology policies; ENERGY; ECONOMY; FUTURE; Chemistry; Electrochemistry; Energy & Fuels